Active measurement mechanism measuring SDN performances - Ming CHEN; Fei DAI; Bo XU; Chang-you XING; Bing LI; Guo-min ZHANG (Tongxin xuebao)
An active SDN measurement mechanism was proposed,which could measure the end-to-end path performance between any two nodes,then the OpenFlow measurement protocol OFMP was designed,and a prototype OFMd was implemented,which could measure multiple performance metrics of the flow between two nodes without changing the switch forwarding rule.The experiment results show that OFMd can acquire multiple end to end path performance metrics only by sending a single probe packet.